Earlier the Better: Interceptive Orthodontics to Correct Various Forms of Malocclusion in a Nine-year-old Boy - Rai, Amita; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha (Orthodontic Journal of Nepal, 2020)
Guidance of eruption and development of the primary, mixed, and permanent dentitions is an integral component of comprehensive oral healthcare for all pediatric dental patients; which should contribute to the development of a permanent dentition that is stable, and functionally and esthetically acceptable. In this case note, we present a case in which various forms of interceptive treatment modalities like; extraction of impacted and erupted supernumerary teeth, correction of anterior crossbite and irregularities using Z-springs and Hawley’s labial bow, and provision of lingual holding arch space maintainer were done to correct malocclusion in a nine-year-old patient. Arch alignment was achieved within seven month of starting of treatment, which was acceptable to the patient.